ANALISIS KEPATUHAN SYARIAH CRYPTOCURRENCY TERHADAP EKOSISTEM EKONOMI SYARIAH - Ja'far Nasution; Azharsyah Ibrahim (STKIP Subang, 2026)
The results show that the Sharia compliance of cryptocurrencies is controversial and contextual. Negatively, cryptocurrencies contain elements of gharar (uncertainty), maysir (speculation), lack clear underlying assets, and have the potential for misuse. Therefore, they tend to be non-compliant with Sharia principles if used as a medium of exchange or speculative instrument. However, on the positive side, cryptocurrencies have the potential to be Sharia-compliant if positioned as digital assets, used for long-term investment, and supported by the transparency of blockchain technology.From the perspective of the maqasid sharia (Islamic principles of protection of wealth), protection of religion (Islamic principles of protection of religion), and protection of reason (Islamic principles of protection of reason) without adequate oversight. Regulations and fatwas in Indonesia demonstrate a dualism, where the use of cryptocurrency as a means of payment is prohibited, but permitted as a commodity under certain conditions.Implications for the sharia economic ecosystem include opportunities in the form of sharia fintech innovation, increased transaction efficiency, and financial inclusion, as well as challenges in the form of legal uncertainty, the risk of sharia non-compliance, and conflicts between fatwas and regulations. Therefore, regulatory harmonization and clear sharia compliance standards are needed so that the use of cryptocurrency can support the sustainable development of the sharia economy.